Simultaneous multiple surface method for the design of new parabolic dish-type concentrator using a Cassegranian approach - Canavarro, Diogo (2022)
Parabolic Dish concentrators are a well-known solution for many applications such as Concentrated Solar Power (CSP), solar metallurgical processes, solar reactors for fuel production, etc. Nevertheless, this technology is facing a tremendous challenge to become more efficient and competitive (especially within CSP field) in comparison with other technologies, namely Central Tower Receivers. A possible path to achieve this goal is to use a Cassegranian approach which enables a top-down design, placing the receiver closer to the ground and with potential higher concentration. In this paper, the theoretical limit of such configurations and a practical solution is presented with a discussion of its advantages and possible drawbacks.